### Advertisement

### Advertisement

Last updated at Aug. 25, 2021 by Teachoo

Transcript

Ex 2.4, 2 Use the Factor Theorem to determine whether g(x) is a factor of p(x) in the following cases: (iii) p(x) = x3 – 4x2 + x + 6 , g(x) = x – 3 Finding remainder when x3 – 4x2 + x + 6 is divided by x – 3 Step 1: Put Divisor = 0 x – 3 = 0 x = 3 Step 2: p(x) = x3 – 4x2 + x + 6 Putting x = 3 p(3) = (3)3 – 4(3)2 + 3 + 6 = 27 – 4(9) + 3 + 6 = 27 – 36 + 3 + 6 = 0 Thus, Remainder = p(3) = 0 Since remainder is zero, x – 3 is a factor of x3 – 4x2 + x + 6

Ex 2.4

Ex 2.4, 1 (i)
Important

Ex 2.4, 1 (ii)

Ex 2.4, 1 (iii)

Ex 2.4, 1 (iv) Important

Ex 2.4, 2 (i)

Ex 2.4, 2 (ii) Important

Ex 2.4, 2 (iii) You are here

Ex 2.4, 3 (i)

Ex 2.4, 3 (ii) Important

Ex 2.4, 3 (iii) Important

Ex 2.4, 3 (iv)

Ex 2.4, 4 (i)

Ex 2.4, 4 (ii) Important

Ex 2.4, 4 (iii)

Ex 2.4, 4 (iv) Important

Ex 2.4, 5 (i)

Ex 2.4, 5 (ii) Important

Ex 2.4, 5 (iii) Important

Ex 2.4, 5 (iv)

About the Author

Davneet Singh

Davneet Singh is a graduate from Indian Institute of Technology, Kanpur. He has been teaching from the past 10 years. He provides courses for Maths and Science at Teachoo.